2020
DOI: 10.1186/s40462-019-0184-2
|View full text |Cite
|
Sign up to set email alerts
|

Contrasted habitats and individual plasticity drive the fine scale movements of juvenile green turtles in coastal ecosystems

Abstract: Background: A strong behavioural plasticity is commonly evidenced in the movements of marine megafauna species, and it might be related to an adaptation to local conditions of the habitat. One way to investigate such behavioural plasticity is to satellite track a large number of individuals from contrasting foraging grounds, but despite recent advances in satellite telemetry techniques, such studies are still very limited in sea turtles.Methods: From 2010 to 2018, 49 juvenile green turtles were satellite track… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 83 publications
(116 reference statements)
7
47
0
Order By: Relevance
“…Prior studies have reported similar home range sizes, with the estimated home ranges for immature green turtles in Hawaii being < 3 km 2 [54] and in Florida were 3 km 2 [42]. Further, turtle core use areas, defined by 50% KDEs, within BIRNM were small (0.3 ± 0.0 km 2 ), similar to that reported by Makowski et al [42] (0.5 ± 0.4 km 2 ) and Chambault et al [55] (0.2 ± 0.3 km 2 ). When resource distributions (i.e., food and shelter) were tightly clustered, space use for immature green turtles was constrained [42,47,54].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Prior studies have reported similar home range sizes, with the estimated home ranges for immature green turtles in Hawaii being < 3 km 2 [54] and in Florida were 3 km 2 [42]. Further, turtle core use areas, defined by 50% KDEs, within BIRNM were small (0.3 ± 0.0 km 2 ), similar to that reported by Makowski et al [42] (0.5 ± 0.4 km 2 ) and Chambault et al [55] (0.2 ± 0.3 km 2 ). When resource distributions (i.e., food and shelter) were tightly clustered, space use for immature green turtles was constrained [42,47,54].…”
Section: Discussionsupporting
confidence: 83%
“…Turtle MCPs and KDEs demonstrated space use was largely located directly south of the island and to the east and west, thus, space use did not perfectly match the predicted relative selection probabilities that were observed across a much broader spatial extent. This may be due to tagging effort being generally located south of the island where green turtle abundances were highest, thus, if immature green turtles exhibit small home ranges as demonstrated here and by Brill et al [54], Makowski et al [42], Griffin et al [47], and Chambault et al [55], we would expect tagged individuals to remain near their capture locations. Further, the RSF model could have been improved with additional covariates that capture additional environmental characteristics (e.g., fetch, wave energy, seagrass total area), ecological processes (e.g., density dependence, predator landscape metrics, [57]), and green turtle foraging strategies.…”
Section: Discussionmentioning
confidence: 57%
“…Once corrected to take the location measurement errors into account, the HR and CA sizes in Martinique are smaller than those found for immature green turtles in Florida (HR: 154 ± 136 km 2 , CA: 22 ± 22 km 2 ; Hart and Fujisaki, 2010), and in North Carolina (HR: 85 ± 48 km 2 ; McClellan and Read, 2009) with Argos-based locations, but consistent with those found for immature and adult green turtles in the Indian Ocean, using Fastloc-GPS data (Chambault et al, 2020;Christiansen et al, 2017).…”
Section: Habitat Usesupporting
confidence: 80%
“…Two turtles settled in the bay of Fort-de-France, which provides algae and seagrass and is fringed by a mangrove. Mangrove compounds have been regularly found in mouth and gut contents of green turtles, and juveniles have already been reported inhabiting mangroves (Chambault et al, 2020;Guebert-Bartholo et al, 2011). A few Martinican turtles may feed in this habitat, in relation with specific physiological adaptations (to digest fruits, algae, and highly energetic animal prey; Bjorndal et al, 2000).…”
Section: Habitat Usementioning
confidence: 99%
See 1 more Smart Citation